(The Development of Extraction of Ginger Oleoresin) - Eko Susanto (Balai Besar Industri Agro, 1989)
Oleoresin ia a product of whole spices which is prepared by extraction of ground spices with solvent. Ginger oleoresin has been known since hundred years ago and now it is still investigated by many researcher in order to increase its quality and quantity. The extraction process of ginger oleoresin is affeted by several factors such as raw material, solvent and the condition of the extraction.